CEREBRAL SINUS VENOUS THROMBOSIS PADA PENDERITA SYSTEMIC LUPUS ERYTHEMATOSUS - Destika Fahrina; Mohammad Arief Rachman Kemal; Adiel Amaris Syah; Melita Melita; Lyna Soertidewi (NEURONA, 2019)
CEREBRAL SINUS VENOUS THROMBOSIS IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTABSTRACTCerebral sinus venous thrombosis (CSVT) may sometimes be associated with autoimmune disorder like systemic lupus erythematosus (SLE). It is characterized by dural venous thrombosis which can cause variety of symptoms including headache, convulsion, motor weakness, and decreased level of consciousness. Thrombosis often occurs in the lower extremities in postpartum women due to prolonged bed rest and caesarean section. We reported a 33-year-old woman, who presented with chief complaint of weakness in the left arm and leg, a history of headache and seizures, the following 3 weeks, she had swelling and pain which started at the tip of the left foot then right leg and to the waist. D-dimer level was increased with positive ANA test. Diagnostic investigations include non-contrast head CT scan, CTV, DSA, Doppler ultrasound and thoracoabdominal vasculare CT. Low molecular weight heparin (LMWH) was given for 5 days, continued with oral anticoagulant.Keywords: Cerebral sinus venous thrombosis, deep vein thrombosis, LMWH, postpartum, systemic lupus erythematosusABSTRAKCerebral sinus venous thrombosis (CSVT) dapat berkaitan dengan gangguan autoimun seperti systemic lupus erythematosus (SLE). Hal ini ditandai adanya trombosis vena dural yang menyebabkan berbagai gejala, seperti nyeri kepala, kejang, kelemahan motorik, serta penurunan kesadaran. Trombosis juga sering terjadi di ekstremitas bawah pada perempuan postpartum akibat tirah baring yang lama dan tindakan seksio sesaria. Dilaporkan kasus seorang perempuan 33 tahun dengan keluhan kelemahan tubuh sisi kiri serta riwayat nyeri kepala dan kejang yang 3 minggu kemudian dijumpai bengkak dan nyeri mulai dari ujung kaki kiri kemudian kaki kanan, hingga naik sampai pinggang. Terdapat peningkatan D-dimer dengan tes ANA (+). Pemeriksaan penunjang diagnostik berupa head CT scan nonkontras, CTV, DSA, USG doppler ekstremitas serta CT vascular thoracoabdominal. Pasien diberikan terapi low molecular weight heparin (LMWH) selama 5 hari, dilanjutkan dengan antikoagulan oral.Kata kunci: Cerebral sinus venous thrombosis, deep vein thrombosis, LMWH, postpartum, systemic lupus erythematosus